How Do Short-Term Incentives Affect Long-Term Productivity? - Almeida, Heitor; Ersahin, Nuri; Fos, Vyacheslav; Irani, Rustom M; Kronlund, Mathias (Review of Financial Studies, 2026)
Abstract Previous research shows that incentives to meet short-term earnings targets can cause firms to increase share buybacks, leading to cuts in investments and employment. Using plant-level census data, we find that incentives to engage in earnings-per-share-motivated buybacks result in lower productivity at both the plant and firm level. We attribute this productivity drop to two mechanisms: reduced investment in productivity-augmenting technology, and inefficient allocation of resources across a firm’s plants. We identify multiple frictions—including labor unions, financial constraints, agency problems, and adjustment costs—that can constrain efficient reallocations across plants and thus exacerbate the consequences of firms’ short-term incentives.